Overview of Environmental Sanitation Rusunawa Oeba Fatubesi Village, Kota Lama District, Kupang City - Shinta Rihi Mangngi; Johny A. R Salmun; Mustakim Sahdan (Lontar : Journal of Community Health, 2022)
Home and environment are basic needs for a family. Flats should be able to become livable dwellings seen from how the environmental sanitation conditions are because the environment plays an essential role in improving the health status of residents and the community around the environment. This study aimed to describe Environmental Sanitation Rusunawa Oeba Fatubesi Village, Kota Lama District, Kupang City; the variables studied were clean water networks, rainwater sewers, wastewater sewers, and garbage dumps, and fire extinguishers. This type of research is descriptive and qualitative. The population is 80 families who live in Oeba flats. Sampling used a total sampling technique so that the sample was 80 households of the residents of the Oeba flats. The results showed that the clean water network had met the requirements (19%), the rainwater sewer did not meet the requirements (88%), the sewerage had met the requirements (100%), and the garbage disposal did not meet the requirements (75%), and fire extinguishers do not meet the requirements (100%). The conclusion from the results of this study is that the environment of Rusunawa Oeba, Fatubesi Village, Kota Lama District, and Kupang City as a whole does not meet the requirements. It is expected that all residents of Rusunawa will take better care of the cleanliness of their living environment by not littering, sorting waste before it is disposed of in landfills, and providing a trash can for each of their dwellings.